(3QhVI GdCYdGe HefRdI GdYQHjI ef Ydhe GdESdGes - (3CHh YHO Gddg TeS GdOjf eMeO Hf Ydj Hf eMeO GdGUHMj GdCfOdSj, GHf GdGRQb,J (B896 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY efGQ GdYQHjI Ydi GdeOM hGdJYXje , hLYdgG eQbGI dage GdSfI GdfHhjI hGdbQBf GdYXje SejJg (B" (3QhVI GdCYdGe HefRdI GdYQHjI ef Ydhe GdESdGe (B" s
(3BNQgG (B:s
(3bGd GHf GdefPQ cGf ecGfg dGjhSY dCMO ai MdbJg hdCjf eYg , jOY CMOge s
(3HgG CKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs